2007
DOI: 10.1534/genetics.107.072009
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Probabilities When Generation Times Are Variable: The Burst–Death Model

Abstract: Estimating the fixation probability of a beneficial mutation has a rich history in theoretical population genetics. Typically, to attain mathematical tractability, we assume that generation times are fixed, while the number of offspring per individual is stochastic. However, fixation probabilities are extremely sensitive to these assumptions regarding life history. In this article, we compute the fixation probability for a ''burstdeath'' life-history model. The model assumes that generation times are exponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…Two striking results have emerged from this study. First, we note that previous work has demonstrated that the fixation probability depends sensitively on this mechanism of the selective advantage (Wahl and Dehaan 2004;Lambert 2006;Hubbarde et al 2007;Parsons and Quince 2007). In particular, when generation times are fixed, mutations that increase fecundity are more likely to fix than mutations that reduce the generation time (Wahl and Dehaan 2004).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Two striking results have emerged from this study. First, we note that previous work has demonstrated that the fixation probability depends sensitively on this mechanism of the selective advantage (Wahl and Dehaan 2004;Lambert 2006;Hubbarde et al 2007;Parsons and Quince 2007). In particular, when generation times are fixed, mutations that increase fecundity are more likely to fix than mutations that reduce the generation time (Wahl and Dehaan 2004).…”
Section: Discussionmentioning
confidence: 81%
“…Recent work, however, has demonstrated that fixation probabilities are extremely sensitive to the underlying life-history model (e.g., Wahl and Dehaan 2004;Lambert 2006;Parsons and Quince 2007;Hubbarde et al 2007). Thus it is critical, for any quantitative estimates of the fixation probability, to find a model that is appropriate for the population and organism under study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As derived previously (Hubbarde et al 2007), for a mutation that first appears at time t 0 during the growth phase, the extinction probabilities are given by Xðt 0 Þ ¼ Gðt 2 l 2 t 0 ; b½Xð0ÞÞ:…”
Section: Discussionmentioning
confidence: 96%
“…The life history of lytic viruses, however, consists of an attachment time, during which the viral particle ''searches'' for a cell to infect, and a lysis time, the time between attachment and host-cell lysis, during which virions accumulate within the cell. Our recent work has developed a life-history model appropriate for lytic viruses, and predicted the fixation probability in the presence or absence of population bottlenecks (Alexander and Wahl, 2008;Hubbarde et al, 2007;Patwa and Wahl, 2008a), neglecting any underlying host-cell dynamics.…”
Section: Introductionmentioning
confidence: 99%